Market Forces and Strategic Determinants of Indonesia’s Shrimp Export Competitiveness in the United States Market (1998–2022) - Kusuma, Septian Gilang; Lusiana, Lusiana; Silaban, Mangatur Ganda (JSM: Jurnal Sains Manajemen, 2025)
Indonesia, as a maritime nation, possesses substantial potential in developing its fisheries sector, with shrimp being one of the country’s most prominent export commodities. Shrimp contributes significantly to Indonesia’s foreign exchange earnings, with major export destinations including the United States, Japan, the Netherlands, and China. This study aims to analyze the determinants of Indonesia’s shrimp exports to the United States during the period 1998–2022. The research employs secondary data sourced from UN Comtrade, the World Bank, and the Ministry of Trade of the Republic of Indonesia. The variables examined include shrimp export quantity, shrimp export price, the rupiah–US dollar exchange rate, U.S. GDP per capita, and crab export prices. The analytical methods consist of descriptive analysis, the Dickey–Fuller (DF) unit root test, the Bounds Test for cointegration, classical assumption tests, and the estimation of an Autoregressive Distributed Lag (ARDL) model. The results indicate that shrimp export quantity and crab export prices exert a significant negative effect on Indonesia’s shrimp export value in both the short and long run. Conversely, shrimp export prices, the rupiah exchange rate, and U.S. GDP per capita demonstrate a significant positive effect on the value of shrimp exports in both time horizons. These findings highlight the multifaceted economic factors shaping Indonesia’s shrimp export performance in the U.S. market and underscore the importance of maintaining competitive prices, stable currency conditions, and responsiveness to demand dynamics in major importing countries